A retrospective study of urological injuries during obstetrics and gynecological procedures - Samal, Sunil Kumar; Rathod, Setu; Thangavel, Kalaivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Urological injury in obstetrics and gynaecology are not uncommon because there is a close anatomical association between reproductive and urological system. The objective of this study was to find out the incidence and types of urological injuries in obstetric and gynaecological procedures, clinical presentation and various management option in a tertiary care hospital. Methods: The study was a retrospective analysis of all obstetric and gynecological surgeries over a period of 6 years from January 2014 to December 2019. Cases with the documented urological injuries during these procedures were analyzed further. Results: Total 8595 patients had undergone different obstetrics and gynecology procedures, out of which 5429 were obstetrics and 3166 were gynecology surgeries. Out of 3166 of gynecology procedures, there were 16 cases (0.5%) of bladder injuries and one case (0.03%) of ureteric injury. Out of 5429 cases of obstetric procedures there were 11 (0.2%) cases of bladder injury and one case (0.01%) of ureteric injury. Conclusions: The incidence urological injuries during obstetrics and gynecological procedures are rare but the morbidity associated these are significant. Therefor surgeons should be more cautious and high degree of suspicion can help in early diagnosis and avoid the sequel.